Adherence to antiretroviral therapy among HIV patients in Ghana: A systematic review and meta-analysis. - Isaac Boadu; Adom Manu; Richmond Nii Okai Aryeetey; Kwame Adjei Kesse; Marijanatu Abdulai; Emmanuel Acheampong; Robert Akparibo (Public Library of Science (PLoS), 2023)
Maintaining a high level of adherence to antiretroviral therapy (ART) is critical to limiting rapid viral replication, drug resistance, and viral transmission. However, ART adherence remains a major challenge in HIV/AIDS treatment success. This systematic review and meta-analysis was aimed to synthesize available evidence on adherence to ART among HIV/AIDS patients in Ghana.This review followed the preferred reporting item for systematic review and meta-analysis (PRISMA) criteria. A comprehensive literature search was done using five online databases (PubMed, Google Scholar, Medline, Africa Index Medicus, and Willey Online Library) from 25th- 30th April 2023 to identify potential studies. In addition, references of related articles were manually searched to further identify relevant studies. Search records were managed in Endnote library where duplicates were removed prior to screening. Studies were eligible for inclusion if they were conducted in Ghana, designed as an observational or experimental study, and explicitly measured adherence to ART, either as a primary or secondary outcome. Studies were excluded if the proportion or prevalence of adherence to ART was not reported.A total number of 126 potential studies were identified from the literature search. Of these, 14 met the inclusion criteria and were included in the Meta-analysis. The studies involved a total number of 4,436 participants. The pooled estimate of adherence to ART was 70% (CI: 58-81%). In subgroup analysis, adolescents and young adults had a lower adherence rate (66%, CI: 46-84%) compared with adults (70%; CI: 58-81%). Publication bias was not observed among studies. The pooled estimate of optimal adherence to ART among HIV patients in Ghana was lower than is recommended (≥95%) to achieve viral suppression. Adherence was lower among young persons living with HIV/AIDS. To achieve the United Nation's Sustainable development goals and the UNAIDS "95-95-95" targets, there is a need to focus on improving adherence interventions among persons living with HIV/AIDS, especially among the younger cohort.